Testing principles application on tests administered to Intermediate Intensive English I students of the Foreign Language Department - Aguilar Guevara, Nubia Maricela; Aragón Cruz, Erick Alexander; Franco Rivera, Karla Jeannette; Miranda Girón, Cecilia (2024)
Assessment is one of the main components of learning and teaching process. It involves any formal or informal activity that is meant to collect information from learners to judge their language performance or language knowledge (Spratt, et al, 2005). In order to collect that information from students, teachers make use of some different tools like paper and pencil tests, role plays and tasks related to real life situations. The most common tool used to gather information is paper and pencil tests. Nevertheless, the information gathered from tests sometimes would not give valid information about students learning due to different factors that affect test design or development such as lack of time resources and the like. Within the educational field tests serve as a tool used to make a decision (Pedhazur et al, 1991). This purpose rules every test, thus teachers are encouraged to determine what students’ needs are and depending on those is how the test should be designed. Researchers discovered important elements that aid this process. Answering four important questions will help to design a quality test. For example, who will take the test (students), why is the test made (purpose), how will the test be evaluated (tasks and grades) and what will be tested (objectives or criteria) are all part of the development stages that a teacher should consider (Fleurquin, 2010). The quality of tests depends directly on its design. Consequently, the design of tests should follow some rules called testing principles in order to make it reliable, valid, useful and practical. Therefore, recognizing what elements are involved in the test design process will make teachers highlight, search for specific information and concentrate on priorities. An important source that eases such process is the course syllabus. Not only because it offers the guidelines for the course but also for test content. In fact, tests must prove a bond with what has been shared in class and what is shown on tests (Kaplan & Saccuzzo, 2008). It is worthless to teach with the test when tests purpose is to measure what has been taught. Along with the syllabus there are some guidelines that become important assets to design a test and that many teachers overlook. In the educational field reliability and validity are the most common testing principles; however, there are others of great importance as well. For instance, within validity: content, construct, criterion, face validity; student-related, teacher-related, administration reliability; authenticity, usefulness, practicality, washback. Applying these, “the cornerstones” (Combee & Hubly, 2007) guarantees better outcomes and an easy way of measuring what students have achieved. Under no circumstance should a test be aimed to flunk students. On the contrary; teachers’ task is to design the fairest test not only because it will benefit students but also because teachers will be able to draw conclusions from a valid test. And such will be only achieved if teachers pay close attention to what is placed on it, which in turn sets a proper expectation from students.